GAMBARAN STATUS GIZI ANAK SEKOLAH DASAR KELAS 3 DI DUSUN PARANG DESA ALLU TAROWANG KECAMATAN TAROWANG KABUPATEN JENEPONTO - Lydia Fanny; Supiati Putri; Nursalim Nursalim; Manjilala Manjilala (Media Gizi Pangan, 2021)
Elementary School Children Grade 3 is a process of growth and development that can be assessed from their nutritional status there are three things that affect the development of one's intelligence, namely nutrition, environment and genetics. This research aims to get an overview of nutritional status in The Village of Parang Village Allu Tarowang District Tarowang Jeneponto Regency. This study is a descriptive study, using 30 samples of Elementary School Children Grade 3 with purposive sampling method. Nutritional status data is measured by anthropometry. The results of the study obtained less weight nutritional status according to the weight/age index as much as 16.7% and normal body weight as much as 83.3%. for the TB/U index is very short as much as 66.7%, short as much as 6.7% and normal as much as 26.7% and the INDEX OF BMI /age malnutrition is less as much as 10.0%, good nutrition as much as 33.3%, nutrition more than 23.3% and obesity 33.3%. Conclusion, that the Nutritional Status of Elementary School Children Grade 3 in The Village of Parang Village Allu Tarowang District Tarowang Jeneponto Regency. 16.7% less weight and 83.3% normal body weight according to height/age, 66.7% very short and 26.7% normal according to height/age, 33.3% good nutrition and 33.3% obesity according to IMT/age. Recommended to the school to improve health and nutrition extension programs for elementary school children Keywords: Nutritional Status  ABSTRAK Anak Sekolah Dasar Kelas 3 merupakan proses tumbuh kembang yang dapat dinilai dari status gizinya ada tiga hal yang mempengaruhi perkembangan kecerdasan seseorang yaitu gizi, lingkungan dan genetik. Penelitian ini bertujuan untuk mendapatkan Gambaran Status Gizi Di Dusun Parang Desa Allu Tarowang Kecamatan Tarowang Kabupaten Jeneponto. penelitian ini merupakan penelitian deskriptif, menggunakan 30 sampel Anak Sekolah Dasar Kelas 3 dengan metode purposive sampling. Data status gizi di ukur dengan antropometri. Hasil penelitian diperoleh status gizi berat badan kurang menurut indeks BB/U sebanyak16.7% dan berat badan normal sebanyak 83.3%. untuk indeks TB/U sangat pendek sebanyak 66.7%, pendek sebanyak 6.7% dan normal sebanyak 26.7% dan indeks IMT/U gizi kurang sebanyak 10.0%, gizi baik sebanyak 33.3%, gizi lebih 23.3% dan obesitas 33.3%.Kesimpulan, bahwa Status Gizi Anak Sekolah Dasar Kelas 3 Di Dusun Parang Desa Allu Tarowang Kecamatan Tarowang Kabupaten Jeneponto. 16.7 % berat badan kurang dan 83.3% berat badan normal menurut BB/U, 66.7% sangat pendek dan 26.7% normal menurut TB/U, 33.3% gizi baik dan 33.3% obesitas menurut IMT/U.Disarankan kepada Pihak sekolah untuk meningkatkan program penyuluhan kesehatan dan gizi bagi Anak Sekolah Dasar.Kata Kunci    : Status Gizi